The checklist of the tribe Olethreutini (Lepidoptera: Tortricidae) of Qinghai-Tibet Plateau - Ma, Shuang; Hu, Zhurong; Dong, Ruiqin; Zhang, Bingyi; Yu, Haili (Zootaxa, 2024)
We present a catalogue of the species of Olethreutini from Qinghai-Tibet Plateau, China with an account of 85 species in 32 genera. One species, Neostatherotis spinosa sp. nov., is described as new; five species, Apotomis generosa (Meyrick, 1909), Celypha sapaecola Razowski, 2009, Dicephalarcha herbosa (Meyrick, 1909), Eppihus hippeus Razowski, 2006, and Eudemis brevisetosa Oku, 2005, are recorded for the first time from China; the female of Demeijerella catharota (Meyrick, 1928) is for the first time. Each species is listed along with specimens examined and geographical distribution. Photographs of adults and genitalia of the new and newly recorded species are provided, along with a map of all collecting sites.